Generation of some methods for solving interval multi-objective linear programming models - Allahdadi, Mehdi; Batamiz, Aida (Opsearch, 2021)
In this paper, we consider interval multi-objective linear programming (IMOLP) models which are very important due to deal with inaccurate data and uncertainties. The aim of this paper is to solve the IMOLP models and obtaining efficient solutions. We first extend Ecker-Kouada method in which the variables are interval, and we introduce interval version of the Ecker-Kouada method which is called I-Ecker-Kouada method. Also, we introduce interval version of Benson’s method (I-Benson) which is not a complicated method. Finally, numerical examples and comparison with other methods are employed to illustrate the advantages of our methods.